A facile strategy for the reduction of graphene oxide and its effect on thermal conductivity of epoxy based composites - F. Xie; S. H. Qi; D. Wu (eXPRESS Polymer Letters)
A facile and efficient approach to reduce graphene oxide with Al particles and potassium hydroxide was developed at moderate temperature and the graphene/epoxy composite was prepared by mould casting method. The as-prepared graphene has been confirmed by Transmission electron microscopy, Fourier transform infrared spectrometer, Raman spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy and Thermal gravimetric analysis. This provides a new green way to synthesize graphene with high surface area and opens another opportunity for the production of graphene. Effects of graphene on thermal conductivity, thermal stability and microstructures of the epoxy-based composite were also investigated. The results showed that thermal conductivity of the composite exhibited a remarkable improvement with increasing content of graphene and thermal conductivity could reach 1.192 W/(m*K) when filled with 3 wt% graphene. Moreover, graphene/epoxy composite exhibits good thermal stability with 3 wt% graphene.